NOD Dendritic Cells Stimulated with Lactobacilli Preferentially Produce IL-10 versus IL-12 and Decrease Diabetes Incidence - Jean N. Manirarora; Sarah A. Parnell; Yoon-Hyeon Hu; Michele M. Kosiewicz; Pascale Alard (Clinical and Developmental Immunology)
Dendritic cells (DCs) from NOD mice produced high levels of IL-12 that induce IFNγ-producing T cells involved in diabetes development. We propose to utilize the microorganism ability to induce tolerogenic DCs to abrogate the proinflammatory process and prevent diabetes development. NOD DCs were stimulated with Lactobacilli (nonpathogenic bacteria targeting TLR2) or lipoteichoic acid (LTA) from Staphylococcus aureus (TLR2 agonist). LTA-treated DCs produced much more IL-12 than IL-10 and accelerated diabetes development when transferred into NOD mice. In contrast, stimulation of NOD DCs with L. casei favored the production of IL-10 over IL-12, and their transfer decreased disease incidence which anti-IL-10R antibodies restored. These data indicated that L. casei can induce NOD DCs to develop a more tolerogenic phenotype via production of the anti-inflammatory cytokine, IL-10. Evaluation of the relative production of IL-10 and IL-12 by DCs may be a very useful means of identifying agents that have therapeutic potential.